CHRONIC PARASITIC SECRETORY SYNDROME BY STRONGYLUS VULGARIS WITH RESISTANCE TO IVERMECTIN IN A RACE THOROUGHBRED EQUINE - Morales B, Abelardo A. (2010)
A thoroughbred race horses, of 2 years old and male was remited. With history of severe emaciation, rough hair and sporadic chronic diarrhea. Previous stool examinations showed HPG 1850 (eggs per g of feces) of Strongylus spp. The employee was treated with Ivermectin 0.2 mg. kg-1 single dose orally. Necropsy was performed and tissue samples were taken for histopathological study, the same as those processed by conventional methods. Additionally, intestinal contents were sampled for parasitological studies. Macroscopic findings were severe emaciation, rough hair and pale mucous membranes. It was noticed gastric ulcer syndrome, hemorrhagic enteritis in the small intestine with chronic focal presence of parasitic forms of 3-5 cm and type cysts, and hemomelasma ilei. The histological sections showed proliferative enteritis by a lymphocytic infiltrate and few eosinophils. Parasitic cysts were observed in the secretory portion (lamina propria). The study showed stool 1050 HPG of Strongylus spp. Parasitic forms were observed and identified as Strongylus vulgaris (Looss, 1990). In conclusion necropsy findings showed a severe parasitic disease syndrome associated with chronic infestation by Strongylus